Dental caries and its relationship with the level of knowledge on the oral health of parents in preschools - Nicollette Vianey Cayo-Tintaya; Tania Adriana Cosme-Raymundo; Rafael Morales-Vadillo (Kiru)
Objective: To determine the relationship between dental caries disease and the level of knowledge about oral health of parents with children from 36 to 71 months of age. Materials and methods: The methodological design was observational, descriptive, cross-sectional, and correlational, and the sample consisted of 123 children enrolled in the IEI N ° 161 "Carapongo" during the year 2018. A validated questionnaire addressed to the parents was carried out, children were evaluated clinically using the ceo-d index, the data were analyzed statistically and for the possible correlation of the variables the Spearman correlation coefficient statistical test was used. Results: A prevalence of dental caries of 89.43% was found for children between 36 and 71 months, (X= 4.03, SD= 2.820) which indicates a moderate level of severity, where children aged 60-71 months obtained a higher ceo-d index. (X= 4.18, SD= 3.16) with respect to the other age groups. Regarding the parents, they presented a level of knowledge in regular oral health, where parents with complete university education presented all, a higher level of knowledge (Good). The correlation of the main variables was p <0.001 and a ρ = -0.906. Conclusions: There is a relationship between dental caries in preschoolers with the level of knowledge of parents, and the latter with their educational level. So it is important that parents have basic knowledge in oral health, hence this is reflected in the oral health of their children.